Modulation of neuronal α1-adrenergic receptor reduces tauopathy and neuroinflammation by inhibiting the STING/NF-κB/NLRP3 signaling pathway in Alzheimer’s disease mice - Bo Li; Li Wang; Yan Xiao; Zhi Tang; Yang Wang; Ting Sun; Xiaolan Qi (Journal of Neuroinflammation)
Abstract Background Neuroinflammation is closely associated with the pathological progression of Alzheimer's disease (AD). The α1-adrenergic receptor (ADRA1), a G protein-coupled receptor, has been identified as a critical therapeutic target in inflammatory disorders. However, its precise mechanistic role in AD pathogenesis remains unclear. Methods To investigate ADRA1's role in AD, we employed 3xTg-AD and wild-type (WT) mice, modulating neuronal ADRA1 expression via intracerebroventricular delivery of adeno-associated viruses. Cognitive function, tau pathology, neuronal morphology, and activation of the STING/NF-κB/NLRP3 signaling pathway were evaluated using behavioral tests, Western blot, Golgi-Cox staining, immunohistochemistry, and immunofluorescence. In vitro AD models were established using Aβ42 oligomer-stimulated SH-SY5Y cells and primary murine neurons, along with SH-SY5Y cells transfected with full-length human tau (SH-SY5Y/htau). Pharmacological antagonists, inhibitors, lentiviral transduction, co-immunoprecipitation, and calcium flux assays were utilized to dissect ADRA1-mediated molecular mechanisms in tauopathy and neuroinflammation. Results Hippocampal ADRA1 expression was significantly elevated in 10-month-old 3xTg-AD mice. Neuronal ADRA1 knockdown suppressed STING/NF-κB/NLRP3 pathway activation, ameliorated tauopathy and neuroinflammation, restored neuronal structure/function, and improved cognitive deficits in 3xTg-AD mice. Conversely, ADRA1 overexpression in C57/BL6 mice induced tauopathy, neuroinflammation, and cognitive impairment. Mechanistically, ADRA1 interacts with CXCR4 to form heterodimers, triggering cytoplasmic Ca2⁺ overload and subsequent STING/NF-κB/NLRP3 pathway activation. Conclusions ADRA1 critically mediates tauopathy and neuroinflammation through STING/NF-κB/NLRP3 signaling. These results identify ADRA1 as a promising therapeutic target for AD prevention and treatment. Graphical Abstract